Environmental Education at School Level : Issues at Glance - Sharma, Kavita (JOURNAL OF INDIAN EDUCATION, 2009)
Environment related problems being complex need complete understanding of social, ecological as well as economic factors of all resources, their short and long term advantages/disadvantages and analysis of the problems and issues arising out of that in order to protect the environment along with taking care of the needs of all living beings through sustainable development. Sustainable development, which is the need of the hour, can be very strongly boosted through Education. A paradigm shift can be provided to it through Environmental Education (EE) which should neither be restricted to water tight compartments of the subject streams nor be dealt in isolation as a separate subject. Emphasis should be on holistic learning with a multi-disciplinary approach. This article explores various issues, dimensions and scope pertaining to environmental education and its implementation at the school level.